Biologics update: IL‐17 inhibitors. Issue 5 (27th October 2021) - Sheth, Samip; Wu, Jashin J.; Han, George Z.
Abstract: Introduction: Psoriasis is an immune‐mediated, multifactorial, systemic disease that has undergone a translational research revolution in the past two decades. As our understanding of the pathogenesis of psoriasis has improved, the interleukin‐17 (IL‐17) pathway has been elucidated as a key driver of chronic inflammation in psoriasis, which contributes to disease onset and progression. Biologic therapies targeting IL‐17 and its receptor have been developed to attenuate the IL‐17 pathway in patients with moderate‐to‐severe plaque psoriasis. This review includes a discussion on the IL‐17 pathway and biologics targeting IL‐17 in clinical trials and practice for the treatment of psoriasis. Objectives: The primary objective of this manuscript is to present safety and efficacy data from clinical trials released in 2018–2021 on IL‐17 therapies for the treatment of psoriasis. An update on the IL‐17 pathway will also be presented to inform the therapeutic development of IL‐17 biologics. Methods: Review of randomized controlled trials on the efficacy and safety of current and upcoming IL‐17 biologics via an electronic literature search on PubMed, The Cochrane Library, and ClinicalTrials.gov . Results: A total of five IL‐17 biologics were included: secukinumab, ixekizumab, broadalumab, ustekinumab, and sonelokimab. The latest clinical trial safety and efficacy data are presented. Conclusion: The introduction of biologic IL‐17 therapies into clinical practice has ushered in a new era of treatment for psoriasis. With a greater understanding of the IL‐17 pathway and new IL‐17 biologics in clinical trials, physicians, and patients will have a greater number of options for more aggressive, targeted management of psoriasis.